Applicability of next-generation risk assessment generic PBK models and their performance within the chemical domain - M. Spaenig; M. W. Ashraf; M. Bouhifd; C. Drake; T. Sobanski; S. E. Escher (Archives of Toxicology, 2026)
Physiologically based kinetic (PBK) models are a cornerstone of in vitro to in vivo extrapolation and are therefore central to next-generation risk assessment (NGRA). This study assesses the performance of a generic, high-throughput PBK model for 26 organic chemicals spanning a wide range of physicochemical properties. Model predictions based on standard in silico and in vitro input parameters were benchmarked against published, chemical-specific PBK models and in vivo kinetic data. Predicted plasma maximum concentrations (Cmax) were within tenfold of in vivo values for 50% of the chemicals and within threefold for 31%. Published PBK models generally showed closer agreement with in vivo Cmax, likely because they incorporate in vivo-derived kinetic parameters or chemical-specific kinetic processes. An analysis of the chemical space revealed a lipophilicity-dependent bias, where Cmax for lipophilic compounds tended to be underpredicted, whereas hydrophilic compounds were overpredicted. No other consistent trends were observed with respect to physicochemical or ADME descriptors, possibly reflecting the limited dataset size. Overall, while the generic PBK model workflow appears suitable for NGRA applications, the observed lipophilicity-dependent bias indicates that chemical-specific corrections or refinements may be required for more accurate predictions.

Closure of the Strait of Hormuz may trigger a bioinvasion super-spreader event - Mario N. Tamburri; James T. Carlton; April M. H. Blakeslee; Alejandro Bortolus; João Canning-Clode; Susana Carvalho; Andrew L. Chang; Ian C. Davidson; Sarah C. Donelan; Lisa A. Drake; Amy E. Fowler; Amy L. Freestone; et al. (Biological Invasions, 2026)

A practical, low-cost floating flux chamber for measuring greenhouse gas emissions from small urban waterbodies - Bryn E. Reynolds; Cole J. C. Van De Ven; Evan Heyes; Jennifer Drake (Environmental Monitoring and Assessment, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The spatial scale of adaptation in pond‐breeding amphibian larvae - Mark C. Urban; Dana L. Drake (Ecology, 2025)
The spatial scale of adaptation is fundamental to our understanding of evolutionary ecology. Traditionally, strong gene flow and weak selection were expected to prevent adaptive evolution at finer spatial scales, but instances of microgeographic adaptation challenge this assumption. We evaluated four alternative predictions about the scale of adaptation to divergent selection from predators for two pond‐breeding amphibians. Common garden experiments revealed that wood frogs developed larger tailfins and higher survival along a spatial cline, indicating the importance of selection and gene flow between and within habitats. Spotted salamanders displayed defensive behaviors and higher survival between ponds. Results suggest that adaptation occurs both between and within habitats such as ponds. Evidence for adaptations within traditional habitats contradicts the traditional notion of the habitat patch as a population. Overall, results compel a greater appreciation of fine‐scaled adaptation in nature, suggest the need for spatially explicit genetic sampling designs, and reject the assumption that populations are always panmictic within habitat patches.

Trade-offs and synergies in the management of environmental pressures: a case study on ship noise mitigation - Karen de Jong; Cathryn C. Murray; Asier Anabitarte; Sarah Bailey; Lisa Drake; Jose A. Fernandes-Salvador; Ida-Maja Hassellov; Nicole Heibeck; Jukka-Pekka Jalkanen; Annukka Lehikoinen; Nathan Merchant; Amanda T. Nylund; et al. (Marine Pollution Bulletin, 2025)

A century of tailings migration from silver mining reduced biodiversity in a Boreal Shield lake - Branaavan Sivarajah; Dale D. Sprague; Drake Hyden; John P. Smol; Joshua Kurek; Jesse C. Vermaire (Environmental Pollution, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Effects of burning on vegetation, soil physicochemistry and prokaryotic microbial communities in surface and subsurface peat - Shaun M. Allingham; Samantha J. Drake; Andrew Ramsey; Chris D. Field; Felix C. Nwaishi; David R. Elliott (Science of The Total Environment, 2024)

P03-11 Assessing kinetic properties in food and feed: tebuconazole case study - C. Drake; M. Spänig; M. Arlt; T. Hoeper; N. Santori; F.M. Buratti; P. Marx-Stölting; E. Testai; S.E. Escher (Toxicology Letters, 2024)

Changes in nitrogen functional genes and microbial populations in soil profiles of a peatland under different burning regimes - Shaun M. Allingham; Samantha J. Drake; Andrew Ramsey; Chris D. Field; Felix C. Nwaishi; David R. Elliott (Applied Soil Ecology, 2024)

15NH4+ uptake and assimilation into amino acids is markedly reduced by elevated CO2 in Scirpus olneyi, a C3 land plant species - Felix D. Dakora; Lee-Ann C. Hayek; Bert G. Drake (South African Journal of Botany, 2024)

Genome analysis of gyroviruses identified in waterfowl in Arizona (USA) - Shawnpreet Sahnan; Diego Olivo; Joy M. Custer; Rohan A. Bandoo; Danny Jackson; Michael C. Lund; Hannah McGraw; Melanie Regney; Victor Aguiar de Souza Penha; Julia Neil; Dean Drake; Kevin McGraw; et al. (Archives of Virology, 2024)

Corrigendum: Turbulent diapycnal fluxes as a pilot Essential Ocean Variable - Arnaud Le Boyer; Nicole Couto; Matthew H. Alford; Henri F. Drake; Cynthia E. Bluteau; Kenneth G. Hughes; Alberto C. Naveira Garabato; Aurélie J. Moulin; Thomas Peacock; Elizabeth C. Fine; Ali Mashayek; Laura Cimoli; et al. (Frontiers in Marine Science, 2024)

Local socioeconomic factors predict urban forest structure and composition across neighborhoods in Syracuse, NY (USA) - Jordan Jessamy; John E. Drake; David J. Nowak; John C. Stella (Landscape and Urban Planning, 2024)

Biochar and vegetation effects on discharge water quality from organic-substrate green roofs - Wenxi Liao; Virinder Sidhu; Melanie A. Sifton; Liat Margolis; Jennifer A.P. Drake; Sean C. Thomas (Science of The Total Environment, 2024)

Intrinsic and Extrinsic Regulation of Water Clarity in a Large, Floodplain River Ecosystem - Alicia M. Carhart; Deanne C. Drake; James R. Fischer; Jeffrey N. Houser; Kathi J. Jankowski; John E. Kalas; Eric M. Lund (Ecosystems, 2024)

Propagating Uncertainty in Predicting Individuals and Means Illustrated with Foliar Chemistry and Forest Biomass - Ruth D. Yanai; John E. Drake; Hannah L. Buckley; Bradley S. Case; Paul J. Lilly; Richard C. Woollons; Javier G. P. Gamarra (Ecosystems, 2024)
Quantifying uncertainty is important to establishing the significance of comparisons, to making predictions with known confidence, and to identifying priorities for investment. However, uncertainty can be difficult to quantify correctly. While sampling error is commonly reported based on replicate measurements, the uncertainty in regression models used to estimate forest biomass from tree dimensions is commonly ignored and has sometimes been reported incorrectly, due either to lack of clarity in recommended procedures or to incentives to underestimate uncertainties. Even more rarely are the uncertainty in predicting individuals and the uncertainty in the mean both recognized for their contributions to overall uncertainty. In this paper, we demonstrate the effect of propagating these two sources of uncertainty using a simple example of calcium concentration of sugar maple foliage, which does not require regression, then the mass of foliage and calcium content of foliage, and finally an entire forest with multiple species and tissue types. The uncertainty due to predicting individuals is greater than the uncertainty in the mean for studies with few trees—up to 30 trees for foliar calcium concentration and 50 trees for foliar mass and calcium content in the data set we analyzed from the Hubbard Brook Experimental Forest. The most correct analysis will take both sources of uncertainty into account, but for practical purposes, country-level reports of uncertainty in carbon stocks can safely ignore the uncertainty in individuals, which becomes negligible with large enough numbers of trees. Ignoring the uncertainty in the mean will result in exaggerated confidence in estimates of forest biomass and carbon and nutrient contents.

Turbulent diapycnal fluxes as a pilot Essential Ocean Variable - Arnaud Le Boyer; Nicole Couto; Matthew H. Alford; Henri F. Drake; Cynthia E. Bluteau; Kenneth G. Hughes; Alberto C. Naveira Garabato; Aurélie J. Moulin; Thomas Peacock; Elizabeth C. Fine; Ali Mashayek; Laura Cimoli; et al. (Frontiers in Marine Science, 2023)
We contend that ocean turbulent fluxes should be included in the list of Essential Ocean Variables (EOVs) created by the Global Ocean Observing System. This list aims to identify variables that are essential to observe to inform policy and maintain a healthy and resilient ocean. Diapycnal turbulent fluxes quantify the rates of exchange of tracers (such as temperature, salinity, density or nutrients, all of which are already EOVs) across a density layer. Measuring them is necessary to close the tracer concentration budgets of these quantities. Measuring turbulent fluxes of buoyancy ( J b ), heat ( J q ), salinity ( J S ) or any other tracer requires either synchronous microscale (a few centimeters) measurements of both the vector velocity and the scalar (e.g., temperature) to produce time series of the highly correlated perturbations of the two variables, or microscale measurements of turbulent dissipation rates of kinetic energy ( ϵ ) and of thermal/salinity/tracer variance ( χ ), from which fluxes can be derived. Unlike isopycnal turbulent fluxes, which are dominated by the mesoscale (tens of kilometers), microscale diapycnal fluxes cannot be derived as the product of existing EOVs, but rather require observations at the appropriate scales. The instrumentation, standardization of measurement practices, and data coordination of turbulence observations have advanced greatly in the past decade and are becoming increasingly robust. With more routine measurements, we can begin to unravel the relationships between physical mixing processes and ecosystem health. In addition to laying out the scientific relevance of the turbulent diapycnal fluxes, this review also compiles the current developments steering the community toward such routine measurements, strengthening the case for registering the turbulent diapycnal fluxes as an pilot Essential Ocean Variable.

Release of live baitfish by recreational anglers drives fish pathogen introduction risk - Margaret C. McEachran; Janice Mladonicky; Catalina Picasso-Risso; D. Andrew R. Drake; Nicholas B.D. Phelps (Preventive Veterinary Medicine, 2023)

Holistic valuation of non-native species requires broadening the tent - Emily M.X. Reed; Todd Schenk; Bryan L. Brown; Haldre Rogers; David C. Haak; Joseph C. Drake; Jacob N. Barney (Trends in Ecology & Evolution, 2023)

A snapshot of online wildlife trade: Australian e-commerce trade of native and non-native pets - Adam Toomes; Stephanie Moncayo; Oliver C. Stringham; Charlotte Lassaline; Lisa Wood; Mariah Millington; Charlotte Drake; Charlotte Jense; Ashley Allen; Katherine G.W. Hill; Pablo García-Díaz; Lewis Mitchell; et al. (Biological Conservation, 2023)

Identification of predominant aroma components of dried pea protein concentrates and isolates - Yaozheng Liu; Dylan C. Cadwallader; MaryAnne Drake (Food Chemistry, 2023)

Disasters collide at the intersection of extreme weather and infectious diseases - John M. Drake; Éric Marty; Kamal J. K. Gandhi; Meredith Welch‐Devine; Brian Bledsoe; Marshall Shepherd; Lynne Seymour; Christine C. Fortuin; Cristian Montes (Ecology Letters, 2023)
Natural disasters interact to affect the resilience and prosperity of communities and disproportionately affect low income families and communities of colour. However, due to lack of a common theoretical framework, these are rarely quantified. Observing severe weather events (e.g. hurricanes and tornadoes) and epidemics (e.g. COVID‐19) unfolding in southeastern US communities led us to conjecture that interactions among catastrophic disturbances might be much more considerable than previously recognized. For instance, hurricane evacuations increase human aggregation, a factor that affects the transmission of acute infections like SARS‐CoV‐2. Similarly, weather damage to health infrastructure can reduce a community's ability to provide services to people who are ill. As globalization and human population and movement continue to increase and weather events are becoming more intense, such complex interactions are expected to magnify and significantly impact environmental and human health.

Early diagenetic processes in an iron-dominated marine depositional system - Maria C. Figueroa; Sebastiaan J. van de Velde; Daniel D. Gregory; Sydnie Lemieux; Jeana Drake; Tina Treude; Nathaniel Kemnitz; William Berelson; Konstantin Choumiline; Steven Bates; Ravi Kukkadapu; Marilyn Fogel; et al. (Geochimica et Cosmochimica Acta, 2023)

Local groundwater decline exacerbates response of dryland riparian woodlands to climatic drought - Jared Williams; John C. Stella; Steven L. Voelker; Adam M. Lambert; Lissa M. Pelletier; John E. Drake; Jonathan M. Friedman; Dar A. Roberts; Michael Bliss Singer (Global Change Biology, 2022)
Dryland riparian woodlands are considered to be locally buffered from droughts by shallow and stable groundwater levels. However, climate change is causing more frequent and severe drought events, accompanied by warmer temperatures, collectively threatening the persistence of these groundwater dependent ecosystems through a combination of increasing evaporative demand and decreasing groundwater supply. We conducted a dendro‐isotopic analysis of radial growth and seasonal (semi‐annual) carbon isotope discrimination (Δ 13 C) to investigate the response of riparian cottonwood stands to the unprecedented California‐wide drought from 2012 to 2019, along the largest remaining free‐flowing river in Southern California. Our goals were to identify principal drivers and indicators of drought stress for dryland riparian woodlands, determine their thresholds of tolerance to hydroclimatic stressors, and ultimately assess their vulnerability to climate change. Riparian trees were highly responsive to drought conditions along the river, exhibiting suppressed growth and strong stomatal closure (inferred from reduced Δ 13 C) during peak drought years. However, patterns of radial growth and Δ 13 C were quite variable among sites that differed in climatic conditions and rate of groundwater decline. We show that the rate of groundwater decline, as opposed to climate factors, was the primary driver of site differences in drought stress, and trees showed greater sensitivity to temperature at sites subjected to faster groundwater decline. Across sites, higher correlation between radial growth and Δ 13 C for individual trees, and higher inter‐correlation of Δ 13 C among trees were indicative of greater drought stress. Trees showed a threshold of tolerance to groundwater decline at 0.5 m year −1 beyond which drought stress became increasingly evident and severe. For sites that exceeded this threshold, peak physiological stress occurred when total groundwater recession exceeded ~3 m. These findings indicate that drought‐induced groundwater decline associated with more extreme droughts is a primary threat to dryland riparian woodlands and increases their susceptibility to projected warmer temperatures.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Greenhouse gases and green roofs: carbon dioxide and methane fluxes in relation to substrate characteristics - Md Abdul Halim; Juliana Vantellingen; Adam S. Gorgolewski; William K. Rose; Jennifer A. P. Drake; Liat Margolis; Sean C. Thomas (Urban Ecosystems, 2022)

Mechanisms underlying lack of functional compensation by insect grazers after tadpole declines in a Neotropical stream - Thomas R. Barnum; John Timothy Wootton; Rebecca J. Bixby; John M. Drake; David Murray‐Stoker; Checo Colón‐Gaud; Amanda T. Rugenski; Therese C. Frauendorf; Scott Connelly; Susan S. Kilham; Matt R. Whiles; Karen R. Lips; et al. (Limnology and Oceanography, 2022)
Resilience of ecosystems to the sudden decline of large‐bodied species is dependent on characteristics of surviving guild members. However, that response may also be mediated by local habitat conditions. Here, we examine the mechanisms behind the observed lack of functional compensation in the algal‐grazing guild by insect grazers following the decline of tadpole grazers in a forested Panamanian stream. We examined: (1) shifts to the individual size distribution of insect grazers between pre‐ and post‐tadpole declines in pool and riffle habitats; (2) tadpole and insect preferences for small‐, medium‐, and large‐sized diatoms; and (3) a causal explanation for why insects did not functionally compensate for tadpole declines. The size distribution of insect grazers following tadpole declines differed between habitats, becoming uniform in pools and more right skewed toward a smaller size class in riffles. In both habitats, tadpoles selectively consumed medium‐sized diatoms but avoided the largest‐sized diatoms. In contrast, grazing insects selectively consumed small‐sized diatoms, but switched to medium‐sized diatoms after tadpole declines. Tadpole declines led to the loss of the strongest interactions between consumers and diatoms. Smaller‐bodied grazing insects could not duplicate these interactions, even with a shift in resource use, providing an explanation for the lack of functional compensation. Furthermore, tadpole declines led to different community structures in each habitat indicating that local habitat conditions mediated the response of surviving guild members. This suggests that the sudden decline of a large‐bodied species does not lead to a singular outcome for the surviving community.

Microgeographic evolution of metabolic physiology in a salamander metapopulation - Sean T. Giery; Dana L. Drake; Mark C. Urban (Ecology, 2021)
The Metabolic Theory of Ecology explains ecological variation spanning taxonomic organization, space, and time based on universal physiological relationships. The theory depends on two core parameters: the normalization constant, a mass‐independent measure of metabolic rate expected to be invariant among similar species, and the scaling coefficient, a measure of metabolic change with body mass commonly assumed to follow the universal 3/4 scaling law. However, emerging evidence for adaptive microevolution of metabolic rates led us to hypothesize that metabolic rate might exhibit evolved variation among populations on microgeographic scales. To evaluate our hypothesis, we explored evidence for evolved variation in the scaling coefficient and normalization constant within a spotted salamander ( Ambystoma maculatum ) metapopulation in Connecticut, USA. We measured standard metabolic rate in common‐garden raised spotted salamanders from 22 different populations and tested for the effects of six ecological variables suspected in advance to select for divergent physiology. We found that metabolic rate rose with body mass with a log‐log slope of 0.97 that was statistically different from the expected 3/4 scaling law. Although we found no evidence for interpopulation variation in the scaling coefficient, we found evidence for interpopulation variation in the normalization constants among populations. Metabolic variation was best explained by differences in population density among ponds. Our results provide mixed support for Metabolic Theory of Ecology assumptions about parameter invariance and illustrate how fundamental physiological processes such as metabolic rate can evolve across microgeographic spatial scales.

Understanding Constraints on Submersed Vegetation Distribution in a Large, Floodplain River: the Role of Water Level Fluctuations, Water Clarity and River Geomorphology - Alicia M. Carhart; John E. Kalas; James T. Rogala; Jason J. Rohweder; Deanne C. Drake; Jeffrey N. Houser (Wetlands, 2021)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Land‐use controls on carbon biogeochemistry in lowland streams of the Congo Basin - Travis W. Drake; David C. Podgorski; Bienvenu Dinga; Jeffrey P. Chanton; Johan Six; Robert G. M. Spencer (Global Change Biology, 2020)
The flux and composition of carbon (C) from land to rivers represents a critical component of the global C cycle as well as a powerful integrator of landscape‐level processes. In the Congo Basin, an expansive network of streams and rivers transport and cycle terrigenous C sourced from the largest swathe of pristine tropical forest on Earth. Increasing rates of deforestation and conversion to agriculture in the Basin are altering the current regime of terrestrial‐to‐aquatic biogeochemical cycling of C. To investigate the role of deforestation on dissolved organic and inorganic C (DOC and DIC, respectively) biogeochemistry in the Congo Basin, six lowland streams that drain catchments of varying forest proportion (12%–77%) were sampled monthly for 1 year. Annual mean concentrations of DOC exhibited an asymptotic response to forest loss, while DIC concentrations increased continuously with forest loss. The isotopic signature of DIC became significantly more enriched with deforestation, indicating a shift in source and processes controlling DIC production. The composition of dissolved organic matter (DOM), as revealed by ultra‐high‐resolution mass spectrometry, indicated that deforested catchments export relatively more aliphatic and heteroatomic DOM sourced from microbial biomass in soils. The DOM compositional results imply that DOM from the deforested sites is more biolabile than DOM from the forest, consistent with the corresponding elevated stream CO 2 concentrations. In short, forest loss results in significant and comprehensive shifts in the C biogeochemistry of the associated streams. It is apparent that land‐use conversion has the potential to dramatically affect the C cycle in the Congo Basin by reducing the downstream flux of stable, vascular‐plant derived DOC while increasing the transfer of biolabile soil C to the atmosphere.

Individual field-collected glassy-winged sharpshooter vectors harbor sequences from two Xylella fastidiosa subspecies - Drake C. Stenger; Lindsey P. Burbank; Rodrigo Krugner; Mark S. Sisterson (European Journal of Plant Pathology, 2019)

Range size and growth temperature influence Eucalyptus species responses to an experimental heatwave - Michael J. Aspinwall; Sebastian Pfautsch; Mark G. Tjoelker; Angelica Vårhammar; Malcolm Possell; John E. Drake; Peter B. Reich; David T. Tissue; Owen K. Atkin; Paul D. Rymer; Siobhan Dennison; Steven C. Van Sluyter (Global Change Biology, 2019)
Understanding forest tree responses to climate warming and heatwaves is important for predicting changes in tree species diversity, forest C uptake, and vegetation–climate interactions. Yet, tree species differences in heatwave tolerance and their plasticity to growth temperature remain poorly understood. In this study, populations of four Eucalyptus species, two with large range sizes and two with comparatively small range sizes, were grown under two temperature treatments (cool and warm) before being exposed to an equivalent experimental heatwave. We tested whether the species with large and small range sizes differed in heatwave tolerance, and whether trees grown under warmer temperatures were more tolerant of heatwave conditions than trees grown under cooler temperatures. Visible heatwave damage was more common and severe in the species with small rather than large range sizes. In general, species that showed less tissue damage maintained higher stomatal conductance, lower leaf temperatures, larger increases in isoprene emissions, and less photosynthetic inhibition than species that showed more damage. Species exhibiting more severe visible damage had larger increases in heat shock proteins (HSPs) and respiratory thermotolerance ( T max ). Thus, across species, increases in HSPs and T max were positively correlated, but inversely related to increases in isoprene emissions. Integration of leaf gas‐exchange, isoprene emissions, proteomics, and respiratory thermotolerance measurements provided new insight into mechanisms underlying variability in tree species heatwave tolerance. Importantly, warm‐grown seedlings were, surprisingly, more susceptible to heatwave damage than cool‐grown seedlings, which could be associated with reduced enzyme concentrations in leaves. We conclude that species with restricted range sizes, along with trees growing under climate warming, may be more vulnerable to heatwaves of the future.

Evaluation of wetted surface area of commercial ships as biofouling habitat flux to the United States - A. Whitman Miller; Ian C. Davidson; Mark S. Minton; Brian Steves; Cameron S. Moser; Lisa A. Drake; Gregory M. Ruiz (Biological Invasions, 2018)

Quantifying the extent of niche areas in the global fleet of commercial ships: the potential for “super-hot spots” of biofouling - Cameron S. Moser; Timothy P. Wier; Matthew R. First; Jonathan F. Grant; Scott C. Riley; Stephanie H. Robbins-Wamsley; Mario N. Tamburri; Gregory M. Ruiz; A. Whitman Miller; Lisa A. Drake (Biological Invasions, 2017)

Positive feedback between chironomids and algae creates net mutualism between benthic primary consumers and producers - Cristina M. Herren; Kyle C. Webert; Michael D. Drake; M. Jake Vander Zanden; Árni Einarsson; Anthony R. Ives; Claudio Gratton (Ecology, 2017)
The chironomids of Lake Mývatn show extreme population fluctuations that affect most aspects of the lake ecosystem. During periods of high chironomid densities, chironomid larvae comprise over 90% of aquatic secondary production. Here, we show that chironomid larvae substantially stimulate benthic gross primary production ( GPP ) and net primary production ( NPP ), despite consuming benthic algae. Benthic GPP in experimental mesocosms with 140,000 larvae/m 2 was 71% higher than in mesocosms with no larvae. Similarly, chlorophyll a concentrations in mesocosms increased significantly over the range of larval densities. Furthermore, larvae showed increased growth rates at higher densities, possibly due to greater benthic algal availability in these treatments. We investigated the hypothesis that larvae promote benthic algal growth by alleviating nutrient limitation, and found that (1) larvae have the potential to cycle the entire yearly external loadings of nitrogen and phosphorus during the growing season, and (2) chlorophyll a concentrations were significantly greater in close proximity to larvae (on larval tubes). The positive feedback between chironomid larvae and benthic algae generated a net mutualism between the primary consumer and primary producer trophic levels in the benthic ecosystem. Thus, our results give an example in which unexpected positive feedbacks can lead to both high primary and high secondary production.

Towards minimizing transport of aquatic nuisance species in ballast water: Do organisms in different size classes respond uniformly to biocidal treatment? - Matthew R. First; Stephanie H. Robbins-Wamsley; Scott C. Riley; Lisa A. Drake (Biological Invasions, 2016)

The effect of silica and maghemite nanoparticles on remediation of Cu(II)-, Mn(II)- and U(VI)-contaminated water by Acutodesmus sp. - Anita Etale; Hlanganani Tutu; Deanne C. Drake (Journal of Applied Phycology, 2016)

Short‐term carbon cycling responses of a mature eucalypt woodland to gradual stepwise enrichment of atmospheric CO 2 concentration - John E. Drake; Catriona A. Macdonald; Mark G. Tjoelker; Kristine Y. Crous; Teresa E. Gimeno; Brajesh K. Singh; Peter B. Reich; Ian C. Anderson; David S. Ellsworth (Global Change Biology, 2016)
Projections of future climate are highly sensitive to uncertainties regarding carbon (C) uptake and storage by terrestrial ecosystems. The Eucalyptus Free‐Air CO 2 Enrichment (Euc FACE ) experiment was established to study the effects of elevated atmospheric CO 2 concentrations (eCO 2 ) on a native mature eucalypt woodland with low fertility soils in southeast Australia. In contrast to other FACE experiments, the concentration of CO 2 at Euc FACE was increased gradually in steps above ambient (+0, 30, 60, 90, 120, and 150 ppm CO 2 above ambient of ~400 ppm), with each step lasting approximately 5 weeks. This provided a unique opportunity to study the short‐term (weeks to months) response of C cycle flux components to eCO 2 across a range of CO 2 concentrations in an intact ecosystem. Soil CO 2 efflux (i.e., soil respiration or R soil ) increased in response to initial enrichment (e.g., +30 and +60 ppm CO 2 ) but did not continue to increase as the CO 2 enrichment was stepped up to higher concentrations. Light‐saturated photosynthesis of canopy leaves ( A sat ) also showed similar stimulation by elevated CO 2 at +60 ppm as at +150 ppm CO 2 . The lack of significant effects of eCO 2 on soil moisture, microbial biomass, or activity suggests that the increase in R soil likely reflected increased root and rhizosphere respiration rather than increased microbial decomposition of soil organic matter. This rapid increase in R soil suggests that under eCO 2, additional photosynthate was produced, transported belowground, and respired. The consequences of this increased belowground activity and whether it is sustained through time in mature ecosystems under eCO 2 are a priority for future research.

Erratum to: Clinical Immunogenicity of rHuPH20, a Hyaluronidase Enabling Subcutaneous Drug Administration - Sanna Rosengren; Samuel S. Dychter; Marie A. Printz; Lei Huang; Richard I. Schiff; Hans-Peter Schwarz; John K. McVey; Fred H. Drake; Dan C. Maneval; Don A. Kennard; Gregory I. Frost; Barry J. Sugarman; et al. (The AAPS Journal, 2015)

Carbon Sequestration in Tidal Salt Marshes of the Northeast United States - Katherine Drake; Holly Halifax; Susan C. Adamowicz; Christopher Craft (Environmental Management, 2015)

Seascape drivers of M acrocystis pyrifera population genetic structure in the northeast P acific - Mattias L. Johansson; Filipe Alberto; Daniel C. Reed; Peter T. Raimondi; Nelson C. Coelho; Mary A. Young; Patrick T. Drake; Christopher A. Edwards; Kyle Cavanaugh; Jorge Assis; Lydia B. Ladah; Tom W. Bell; et al. (Molecular Ecology, 2015)
At small spatial and temporal scales, genetic differentiation is largely controlled by constraints on gene flow, while genetic diversity across a species' distribution is shaped on longer temporal and spatial scales. We assess the hypothesis that oceanographic transport and other seascape features explain different scales of genetic structure of giant kelp, M acrocystis pyrifera . We followed a hierarchical approach to perform a microsatellite‐based analysis of genetic differentiation in M acrocystis across its distribution in the northeast P acific. We used seascape genetic approaches to identify large‐scale biogeographic population clusters and investigate whether they could be explained by oceanographic transport and other environmental drivers. We then modelled population genetic differentiation within clusters as a function of oceanographic transport and other environmental factors. Five geographic clusters were identified: A laska/ C anada, central C alifornia, continental S anta B arbara, C alifornia C hannel I slands and mainland southern C alifornia/ B aja C alifornia peninsula. The strongest break occurred between central and southern C alifornia, with mainland S anta B arbara sites forming a transition zone between the two. Breaks between clusters corresponded approximately to previously identified biogeographic breaks, but were not solely explained by oceanographic transport. An isolation‐by‐environment ( IBE ) pattern was observed where the northern and southern C hannel I slands clustered together, but not with closer mainland sites, despite the greater distance between them. The strongest environmental association with this IBE pattern was observed with light extinction coefficient, which extends suitable habitat to deeper areas. Within clusters, we found support for previous results showing that oceanographic connectivity plays an important role in the population genetic structure of M acrocystis in the Northern hemisphere.

Clinical Immunogenicity of rHuPH20, a Hyaluronidase Enabling Subcutaneous Drug Administration - Sanna Rosengren; Samuel S. Dychter; Marie A. Printz; Lei Huang; Richard I. Schiff; Hans-Peter Schwarz; John K. McVey; Fred H. Drake; Dan C. Maneval; Don A. Kennard; Gregory I. Frost; Barry J. Sugarman; et al. (The AAPS Journal, 2015)

Evidence for the persistence of food web structure after amphibian extirpation in a Neotropical stream - Thomas R. Barnum; John M. Drake; Checo Colón-Gaud; Amanda T. Rugenski; Therese C. Frauendorf; Scott Connelly; Susan S. Kilham; Matt R. Whiles; Karen R. Lips; Catherine M. Pringle (Ecology, 2015)
Species losses are predicted to simplify food web structure, and disease‐driven amphibian declines in Central America offer an opportunity to test this prediction. Assessment of insect community composition, combined with gut content analyses, was used to generate periphyton–insect food webs for a Panamanian stream, both pre‐ and post‐amphibian decline. We then used network analysis to assess the effects of amphibian declines on food web structure. Although 48% of consumer taxa, including many insect taxa, were lost between pre‐ and post‐amphibian decline sampling dates, connectance declined by less than 3%. We then quantified the resilience of food web structure by calculating the number of expected cascading extirpations from the loss of tadpoles. This analysis showed the expected effects of species loss on connectance and linkage density to be more than 60% and 40%, respectively, than were actually observed. Instead, new trophic linkages in the post‐decline food web reorganized the food web topology, changing the identity of “hub” taxa, and consequently reducing the effects of amphibian declines on many food web attributes. Resilience of food web attributes was driven by a combination of changes in consumer diets, particularly those of insect predators, as well as the appearance of generalist insect consumers, suggesting that food web structure is maintained by factors independent of the original trophic linkages.

Mesoporous Silica Nanoparticles for the Adsorptive Removal of Cu(II), Mn(II), and U(VI) from Acid Mine Drainage - Anita Etale; Hlanganani Tutu; Deanne C. Drake (Mine Water and the Environment, 2015)

New insights into the genetic structure of Araucaria araucana forests based on molecular and historic evidences - M. A. Martín; C. Mattioni; I. Lusini; J. R. Molina; M. Cherubini; F. Drake; M. A. Herrera; F. Villani; L. M. Martín (Tree Genetics & Genomes, 2014)

3D imaging provides a high-resolution, volumetric approach for analyzing biofouling - Matthew R. First; Steven A. Policastro; Matthew J. Strom; Scott C. Riley; Stephanie H. Robbins-Wamsley; Lisa A. Drake (Biofouling, 2014)

Scaffold-Free Tissue Engineering: Organization of the Tissue Cytoskeleton and Its Effects on Tissue Shape - Caitlin A. Czajka; Agnes Nagy Mehesz; Thomas C. Trusk; Michael J. Yost; Christopher J. Drake (Annals of Biomedical Engineering, 2014)

Early Airway Structural Changes in Cystic Fibrosis Pigs as a Determinant of Particle Distribution and Deposition - Maged Awadalla; Shinjiro Miyawaki; Mahmoud H. Abou Alaiwa; Ryan J. Adam; Drake C. Bouzek; Andrew S. Michalski; Matthew K. Fuld; Karen J. Reynolds; Eric A. Hoffman; Ching-Long Lin; David A. Stoltz (Annals of Biomedical Engineering, 2014)

Transformation of Althaea officinalis L. by Agrobacterium rhizogenes for the production of transgenic roots expressing the anti-HIV microbicide cyanovirin-N - Pascal M. W. Drake; Luisa de Moraes Madeira; Tim H. Szeto; Julian K-C. Ma (Transgenic Research, 2013)

Building local environmental knowledge in undergraduates with experiential wilderness skills and awareness training: the case of environmental sentinels - Jacob C. Brenner; Jason G. Hamilton; Tim Drake; Jed Jordan (Journal of Environmental Studies and Sciences, 2013)

Public preferences for production of local and global ecosystem services - Ben Drake; James C. R. Smart; Mette Termansen; Klaus Hubacek (Regional Environmental Change, 2013)

The propagation and dispersal of misinformation in ecology: Is there a relationship between citation accuracy and journal impact factor? - D. C. Drake; B. Maritz; S. M. Jacobs; C. J. Crous; A. Engelbrecht; A. Etale; M. J. Fourie; D. G. Furniss; S. L. Scott; S. Parusnath; D. R. Tye (Hydrobiologia, 2013)

Hybrid mouse diversity panel: a panel of inbred mouse strains suitable for analysis of complex genetic traits - Anatole Ghazalpour; Christoph D. Rau; Charles R. Farber; Brian J. Bennett; Luz D. Orozco; Atila van Nas; Calvin Pan; Hooman Allayee; Simon W. Beaven; Mete Civelek; Richard C. Davis; Thomas A. Drake; et al. (Mammalian Genome, 2012)

An exotic Australian Acacia fixes more N than a coexisting indigenous Acacia in a South African riparian zone - Donovan R. C. Tye; D. C. Drake (Plant Ecology, 2012)

Nitrogen source and p CO 2 synergistically affect carbon allocation, growth and morphology of the coccolithophore E miliania huxleyi : potential implications of ocean acidification for the carbon cycle - Stephane C. Lefebvre; Ina Benner; Jonathon H. Stillman; Alexander E. Parker; Michelle K. Drake; Pascale E. Rossignol; Kristine M. Okimura; Tomoko Komada; Edward J. Carpenter (Global Change Biology, 2012)
Coccolithophores are unicellular phytoplankton that produce calcium carbonate coccoliths as an exoskeleton. E miliania huxleyi , the most abundant coccolithophore in the world's ocean, plays a major role in the global carbon cycle by regulating the exchange of CO 2 across the ocean‐atmosphere interface through photosynthesis and calcium carbonate precipitation. As CO 2 concentration is rising in the atmosphere, the ocean is acidifying and ammonium ( NH 4 + ) concentration of future ocean water is expected to rise. The latter is attributed to increasing anthropogenic nitrogen ( N ) deposition, increasing rates of cyanobacterial N 2 fixation due to warmer and more stratified oceans, and decreased rates of nitrification due to ocean acidification. Thus, future global climate change will cause oceanic phytoplankton to experience changes in multiple environmental parameters including CO 2 , pH , temperature and nitrogen source. This study reports on the combined effect of elevated p CO 2 and increased NH 4 + to nitrate ( NO 3 − ) ratio ( NH 4 + / NO 3 − ) on E . huxleyi, maintained in continuous cultures for more than 200 generations under two p CO 2 levels and two different N sources. Herein, we show that NH 4 + assimilation under N ‐replete conditions depresses calcification at both low and high p CO 2 , alters coccolith morphology, and increases primary production. We observed that N source and p CO 2 synergistically drive growth rates, cell size, and the ratio of inorganic to organic carbon. These responses to N source suggest that, compared to increasing CO 2 alone, a greater disruption of the organic carbon pump could be expected in response to the combined effect of increased NH 4 + / NO 3 − ratio and CO 2 level in the future acidified ocean. Additional experiments conducted under lower nutrient conditions are needed prior to extrapolating our findings to the global oceans. Nonetheless, our results emphasize the need to assess combined effects of multiple environmental parameters on phytoplankton biology to develop accurate predictions of phytoplankton responses to ocean acidification.

Generation of transgenic plants expressing plasma membrane-bound antibodies to the environmental pollutant microcystin-LR - Tommaso Barbi; Pascal M. W. Drake; Matthew Drever; Craig J. van Dolleweerd; Andrew R. Porter; Julian K-C. Ma (Transgenic Research, 2011)

Critical patch size generated by Allee effect in gypsy moth, Lymantria dispar (L.) - E. Vercken; A. M. Kramer; P. C. Tobin; J. M. Drake (Ecology Letters, 2011)
Ecology Letters (2011) 14: 179–186 Abstract Allee effects are important dynamical mechanisms in small‐density populations in which per capita population growth rate increases with density. When positive density dependence is sufficiently severe (a ‘strong’ Allee effect), a critical density arises below which populations do not persist. For spatially distributed populations subject to dispersal, theory predicts that the occupied area also exhibits a critical threshold for population persistence, but this result has not been confirmed in nature. We tested this prediction in patterns of population persistence across the invasion front of the European gypsy moth ( Lymantria dispar ) in the United States in data collected between 1996 and 2008. Our analysis consistently provided evidence for effects of both population area and density on persistence, as predicted by the general theory, and confirmed here using a mechanistic model developed for the gypsy moth system. We believe this study to be the first empirical documentation of critical patch size induced by an Allee effect.

Shallow coastal lakes in New Zealand: current conditions, catchment-scale human disturbance, and determination of ecological integrity - D. C. Drake; David Kelly; Marc Schallenberg (Hydrobiologia, 2011)

Optimisation of contained Nicotiana tabacum cultivation for the production of recombinant protein pharmaceuticals - Richard Colgan; Christopher J. Atkinson; Matthew Paul; Sally Hassan; Pascal M. W. Drake; Amy L. Sexton; Simon Santa-Cruz; David James; Keith Hamp; Colin Gutteridge; Julian K-C. Ma (Transgenic Research, 2010)

The Prevalence of Fentanyl in Drug-Related Deaths in Philadelphia 2004–2006 - Stella C. Wong; Lisa Mundy; Rebecca Drake; John A. Curtis; William E. Wingert (Journal of Medical Toxicology, 2010)

Effects of grape xylem sap and cell wall constituents on in vitro growth, biofilm formation and cellular aggregation of Xylella fastidiosa - Davis W. Cheng; Hong Lin; M. Andrew Walker; Drake C. Stenger; Edwin L. Civerolo (European Journal of Plant Pathology, 2009)

Salt marsh ecosystem biogeochemical responses to nutrient enrichment: a paired 15 N tracer study - D. C. Drake; Bruce J. Peterson; Kari A. Galván; Linda A. Deegan; Charles Hopkinson; J. Michael Johnson; K. Koop-Jakobsen; Lynsey E. Lemay; Christian Picard (Ecology, 2009)
We compared processing and fate of dissolved NO 3 − in two New England salt marsh ecosystems, one receiving natural flood tide concentrations of ∼1–4 μmol NO 3 − /L and the other receiving experimentally fertilized flood tides containing ∼70–100 μmol NO 3 − /L. We conducted simultaneous 15 NO 3 − (isotope) tracer additions from 23 to 28 July 2005 in the reference (8.4 ha) and fertilized (12.4 ha) systems to compare N dynamics and fate. Two full tidal cycles were intensively studied during the paired tracer additions. Resulting mass balances showed that essentially 100% (0.48–0.61 mol NO 3 ‐N·ha −1 ·h −1 ) of incoming NO 3 − was assimilated, dissimilated, sorbed, or sedimented (processed) within a few hours in the reference system when NO 3 − concentrations were 1.3–1.8 μmol/L. In contrast, only 50–60% of incoming NO 3 − was processed in the fertilized system when NO 3 − concentrations were 84–96 μmol/L; the remainder was exported in ebb tidewater. Gross NO 3 − processing was ∼40 times higher in the fertilized system at 19.34–24.67 mol NO 3 ‐N·ha −1 ·h −1 . Dissimilatory nitrate reduction to ammonium was evident in both systems during the first 48 h of the tracer additions but 15 NO 3 − was exported as 15 NH 4 + . Nitrification rates calculated by 15 NO 3 − dilution were 6.05 and 4.46 mol·ha −1 ·h −1 in the fertilized system but could not be accurately calculated in the reference system due to rapid ( 3 − turnover. Over the five‐day paired tracer addition, sediments sequestered a small fraction of incoming NO 3 − , although the efficiency of sequestration was 3.8% in the reference system and 0.7% in the fertilized system. Gross sediment N sequestration rates were similar at 13.5 and 12.6 mol·ha −1 ·d −1 , respectively. Macrophyte NO 3 − uptake efficiency, based on tracer incorporation in aboveground tissues, was considerably higher in the reference system (16.8%) than the fertilized system (2.6%), although bulk uptake of NO 3 − by plants was lower in the reference system (1.75 mol NO 3 − ·ha −1 ·d −1 ) than the fertilized system (∼10 mol NO 3 − ·ha −1 ·d −1 ). Nitrogen processing efficiency decreased with NO 3 − load in all pools, suggesting that the nutrient processing capacity of the marsh ecosystem was exceeded in the fertilized marsh.

Does deep soil N availability sustain long‐term ecosystem responses to elevated CO 2 ? - DUNCAN C. McKINLEY; JULIO C. ROMERO; BRUCE A. HUNGATE; BERT G. DRAKE; JAMES P. MEGONIGAL (Global Change Biology, 2009)
A scrub‐oak woodland has maintained higher aboveground biomass accumulation after 11 years of atmospheric CO 2 enrichment (ambient +350 μmol CO 2 mol −1 ), despite the expectation of strong nitrogen (N) limitation at the site. We hypothesized that changes in plant available N and exploitation of deep sources of inorganic N in soils have sustained greater growth at elevated CO 2 . We employed a suite of assays performed in the sixth and 11th year of a CO 2 enrichment experiment designed to assess soil N dynamics and N availability in the entire soil profile. In the 11th year, we found no differences in gross N flux, but significantly greater microbial respiration ( P≤ 0.01) at elevated CO 2 . Elevated CO 2 lowered extractable inorganic N concentrations ( P =0.096) considering the whole soil profile (0–190 cm). Conversely, potential net N mineralization, although not significant in considering the entire profile ( P =0.460), tended to be greater at elevated CO 2 . Ion‐exchange resins placed in the soil profile for approximately 1 year revealed that potential N availability at the water table was almost 3 × greater than found elsewhere in the profile, and we found direct evidence using a 15 N tracer study that plants took up N from the water table. Increased microbial respiration and shorter mean residence times of inorganic N at shallower depths suggests that enhanced SOM decomposition may promote a sustained supply of inorganic N at elevated CO 2 . Deep soil N availability at the water table is considerable, and provides a readily available source of N for plant uptake. Increased plant growth at elevated CO 2 in this ecosystem may be sustained through greater inorganic N supply from shallow soils and N uptake from deep soil.

Climate change, conservation and management: an assessment of the peer-reviewed scientific journal literature - Adam Felton; Joern Fischer; David B. Lindenmayer; Rebecca Montague-Drake; Arianne R. Lowe; Debbie Saunders; Annika M. Felton; Will Steffen; Nicola T. Munro; Kara Youngentob; Jake Gillen; Phil Gibbons; et al. (Biodiversity and Conservation, 2009)

Potential health impacts of heavy-metal exposure at the Tar Creek Superfund site, Ottawa County, Oklahoma - John S. Neuberger; Stephen C. Hu; K. David Drake; Rebecca Jim (Environmental Geochemistry and Health, 2009)

Wheat streak mosaic virus genotypes introduced to Argentina are closely related to isolates from the American Pacific Northwest and Australia - Drake C. Stenger; Roy French (Archives of Virology, 2009)

Disturbance, rainfall and contrasting species responses mediated aboveground biomass response to 11 years of CO 2 enrichment in a Florida scrub‐oak ecosystem - TROY J. SEILER; DANIEL P. RASSE; JIAHONG LI; PAUL DIJKSTRA; HANS P. ANDERSON; DAVID P. JOHNSON; THOMAS L. POWELL; BRUCE A. HUNGATE; C. ROSS HINKLE; BERT G. DRAKE (Global Change Biology, 2009)
This study reports the aboveground biomass response of a fire‐regenerated Florida scrub‐oak ecosystem exposed to elevated CO 2 (1996–2007), from emergence after fire through canopy closure. Eleven years exposure to elevated CO 2 caused a 67% increase in aboveground shoot biomass. Growth stimulation was sustained throughout the experiment; although there was significant variability between years. The absolute stimulation of aboveground biomass generally declined over time, reflecting increasing environmental limitations to long‐term growth response. Extensive defoliation caused by hurricanes in September 2004 was followed by a strong increase in shoot density in 2005 that may have resulted from reopening the canopy and relocating nitrogen from leaves to the nutrient‐poor soil. Biomass response to elevated CO 2 was driven primarily by stimulation of growth of the dominant species, Quercus myrtifolia , while Quercus geminata , the other co‐dominant oak, displayed no significant CO 2 response. Aboveground growth also displayed interannual variation, which was correlated with total annual rainfall. The rainfall × CO 2 interaction was partially masked at the community level by species‐specific responses: elevated CO 2 had an ameliorating effect on Q. myrtifolia growth under water stress. The results of this long‐term study not only show that atmospheric CO 2 concentration had a consistent stimulating effect on aboveground biomass production, but also showed that available water is the primary driver of interannual variation in shoot growth and that the long‐term response to elevated CO 2 may have been caused by other factors such as nutrient limitation and disturbance.

Cocaine self-administration on a hold-down schedule of reinforcement in rats - Drake Morgan; Yu Liu; Erik B. Oleson; David C. S. Roberts (Psychopharmacology, 2009)

Complete nucleotide sequence of a maize chlorotic mottle virus isolate from Nebraska - Drake C. Stenger; Roy French (Archives of Virology, 2008)

Cross-sensitization of the reinforcing effects of cocaine and amphetamine in rats - Yu Liu; Drake Morgan; David C. S. Roberts (Psychopharmacology, 2007)

Effects of the river discharge management on the nursery function of the Guadalquivir river estuary (SW Spain) - Carlos Fernández-Delgado; F. Baldó; C. Vilas; D. García-González; J. A. Cuesta; E. González-Ortegón; P. Drake (Hydrobiologia, 2007)

Production of Landsat ETM+ reference imagery of burned areas within Southern African savannahs: comparison of methods and application to MODIS - A. M. S. Smith; N. A. Drake; M. J. Wooster; A. T. Hudak; Z. A. Holden; C. J. Gibbons (International Journal of Remote Sensing, 2007)

Spatio‐temporal distribution of early life stages of the European anchovy Engraulis encrasicolus L. within a European temperate estuary with regulated freshwater inflow: effects of environmental variables - P. Drake; A. Borlán; E. González‐Ortegón; F. Baldó; C. Vilas; C. Fernández‐Delgado (Journal of Fish Biology, 2007)
The spatio‐temporal distribution of the anchovy Engraulis encrasicolus in its early life stages was related to environmental conditions within the Guadalquivir River estuary (south‐west, Spain) by monthly field surveys during nine periods of recruitment (May 1997 to December 2005). Anchovy post‐larvae showed a consistent seasonal pattern of abundance throughout the study period: each year, a high anchovy recruitment period (HARP) occurred from late May to November, with a main peak in July, coinciding with the period when environmental conditions were more stable. Results of stepwise multiple regression analysis indicates that density of its main prey, Mesopodopsis slabberi, explained 45% of total anchovy density variance. Furthermore, after removing the effect of this variable, interannual differences in the anchovy estuarine recruitment were not significant. Clear spatial and tidal trends were also observed for both prey and predator: at each sampling date, density decreased from the outer to inner estuary; at each sampling site, density was higher during ebbs than during floods. Field distributions related to environmental gradients during HARP indicated that the populations of E. encrasicolus and M. slabberi seemed to hold a steady position at a point on the salinity gradient by longitudinal displacement within the estuary. Since freshwater management actions affect the longitudinal position of the salinity gradient as well as the input of nutrients to the estuary and adjacent coastal areas, it is hypothesized that this factor may also be relevant to anchovy recruitment.

Root biomass and nutrient dynamics in a scrub-oak ecosystem under the influence of elevated atmospheric CO2 - Alisha Lea Pagel Brown; Frank P. Day; Bruce A. Hungate; Bert G. Drake; C. Ross Hinkle (Plant and Soil, 2007)

Discrete-trials heroin self-administration produces sensitization to the reinforcing effects of cocaine in rats - Sara J. Ward; Christopher Läck; Drake Morgan; David C. S. Roberts (Psychopharmacology, 2006)

The Decapod Custacean Community of the Guadalquivir Estuary (SW Spain): Seasonal and Inter-Year Changes in Community Structure - J. A. Cuesta; E. González-Ortegón; A. Rodríguez; F. Baldó; C. Vilas; P. Drake (Hydrobiologia, 2006)

Elevated CO 2 increases the long‐term decomposition rate of Quercus myrtifolia leaf litter - MYRA C. HALL; PETER STILING; DANIEL C. MOON; BERT G. DRAKE; MARK D. HUNTER (Global Change Biology, 2006)
Decomposition of Quercus myrtifolia leaf litter in a Florida scrub oak community was followed for 3 years in two separate experiments. In the first experiment, we examined the effects CO 2 and herbivore damage on litter quality and subsequent decomposition. Undamaged, chewed and mined litter generated under ambient and elevated (ambient+350 ppm V) CO 2 was allowed to decompose under ambient conditions for 3 years. Initial litter chemistry indicated that CO 2 levels had minor effects on litter quality. Litter damaged by leaf miners had higher initial concentrations of condensed tannins and nitrogen (N) and lower concentrations of hemicellulose and C : N ratios compared with undamaged and chewed litter. Despite variation in litter quality associated with CO 2 , herbivory, and their interaction, there was no subsequent effect on rates of decomposition under ambient atmospheric conditions. In the second experiment, we examined the effects of source (ambient and elevated) of litter and decomposition site (ambient and elevated) on litter decomposition and N dynamics. Litter was not separated by damage type. The litter from both elevated and ambient CO 2 was then decomposed in both elevated and ambient CO 2 chambers. Initial litter chemistry indicated that concentrations of carbon (C), hemicellulose, and lignin were higher in litter from elevated than ambient CO 2 chambers. Despite differences in C and fiber concentrations, litter from ambient and elevated CO 2 decomposed at comparable rates. However, the atmosphere in which the decomposition took place resulted in significant differences in rates of decomposition. Litter decomposing under elevated CO 2 decomposed more rapidly than litter under ambient CO 2 , and exhibited higher rates of mineral N accumulation. The results suggest that the atmospheric conditions during the decomposition process have a greater impact on rates of decomposition and N cycling than do the atmospheric conditions under which the foliage was produced.

Potential Invasion of Microorganisms and Pathogens via ‘Interior Hull Fouling’: Biofilms Inside Ballast Water Tanks - Lisa A. Drake; Anne E. Meyer; Robert L. Forsberg; Robert E. Baier; Martina A. Doblin; Stefan Heinemann; William P. Johnson; Michael Koch; Parke A. Rublee; Fred C. Dobbs (Biological Invasions, 2005)

Effects of Elevated CO2 and Herbivore Damage on Litter Quality in a Scrub Oak Ecosystem - Myra C. Hall; Peter Stiling; Bruce A. Hungate; Bert G. Drake; Mark D. Hunter (Journal of Chemical Ecology, 2005)

Effects of extended-access self-administration and deprivation on breakpoints maintained by cocaine in rats - Yu Liu; David C. S. Roberts; Drake Morgan (Psychopharmacology, 2005)

Factors associated with time to availability for cases reported to population-based cancer registries⋆ - Julie Smith-Gagen; Rosemary D. Cress; Christiana M. Drake; Martha C. Felter; James J. Beaumont (Cancer Causes & Control, 2005)

Comparative Aquatic Toxicity Evaluation of 2-(Thiocyanomethylthio)benzothiazole and Selected Degradation Products Using Ceriodaphnia dubia - S. T. Nawrocki; K. D. Drake; C. F. Watson; G. D. Foster; K. J. Maier (Archives of Environmental Contamination and Toxicology, 2005)

Binge self-administration and deprivation produces sensitization to the reinforcing effects of cocaine in rats - Drake Morgan; Mark A. Smith; David C. S. Roberts (Psychopharmacology, 2005)

Effects of elevated CO2 on foliar quality and herbivore damage in a scrub oak ecosystem - Myra C. Hall; Peter Stiling; Daniel C. Moon; Bert G. Drake; Mark D. Hunter (Journal of Chemical Ecology, 2005)

Induced Defensive Response of Myrtle Oak to Foliar Insect Herbivory in Ambient and Elevated Co2 - Anthony M. Rossi; Peter Stiling; Daniel C. Moon; Maria V. Cattell; Bert G. Drake (Journal of Chemical Ecology, 2004)

Effects of positive allosteric modulators of the GABA B receptor on cocaine self-administration in rats - Mark A. Smith; David L. Yancey; Drake Morgan; Yu Liu; Wolfgang Froestl; David C. S. Roberts (Psychopharmacology, 2004)

The use of reference strand‐mediated conformational analysis for the study of cheetah ( Acinonyx jubatus ) feline leucocyte antigen class II DRB polymorphisms - G. J. C. Drake; L. J. Kennedy; H. K. Auty; R. Ryvar; W. E. R. Ollier; A. C. Kitchener; A. R. Freeman; A. D. Radford (Molecular Ecology, 2004)
There is now considerable evidence to suggest the cheetah ( Acinonyx jubatus ) has limited genetic diversity. However, the extent of this and its significance to the fitness of the cheetah population, both in the wild and captivity, is the subject of some debate. This reflects the difficulty associated with establishing a direct link between low variability at biologically significant loci and deleterious aspects of phenotype in this, and other, species. Attempts to study one such region, the feline leucocyte antigen (FLA), are hampered by a general reliance on cloning and sequencing which is expensive, labour‐intensive, subject to PCR artefact and always likely to underestimate true variability. In this study we have applied reference strand‐mediated conformational analysis (RSCA) to determine the FLA–DRB phenotypes of 25 cheetahs. This technique was rapid, repeatable and less prone to polymerase chain reaction (PCR)‐induced sequence artefacts associated with cloning. Individual cheetahs were shown to have up to three FLA–DRB genes. A total of five alleles were identified (DRB*ha14–17 and DRB*gd01) distributed among four genotypes. Fifteen cheetahs were DRB*ha14/ha15/ha16/ha17, three were DRB*ha15/ha16/ha17, six were DRB*ha14/ha16/ha17 and one was DRB*ha14/ha15/ha16/ha17/gd01. Sequence analysis of DRB*gd01 suggested it was a recombinant of DRB*ha16 and DRB*ha17. Generation of new alleles is difficult to document, and the clear demonstration of such an event is unusual. This study confirms further the limited genetic variability of the cheetah at a biologically significant region. RSCA will facilitate large‐scale studies that will be needed to correlate genetic diversity at such loci with population fitness in the cheetah and other species.

Effects of elevated atmospheric CO 2 on net ecosystem CO 2 exchange of a scrub–oak ecosystem - Graham J. Hymus; David P. Johnson; Sabina Dore; Hans P. Anderson; C. Ross Hinkle; Bert G. Drake (Global Change Biology, 2003)
We report the results of a 2‐year study of effects of the elevated (current ambient plus 350 μmol CO 2 mol −1 ) atmospheric CO 2 concentration ( C a ) on net ecosystem CO 2 exchange ( NEE ) of a scrub–oak ecosystem. The measurements were made in open‐top chambers (OTCs) modified to function as open gas‐exchange systems. The OTCs enclosed samples of the ecosystem (ca. 10 m 2 surface area) that had regenerated after a fire, 5 years before, in either current ambient or elevated C a . Throughout the study, elevated C a increased maximum NEE ( NEE max ) and the apparent quantum yield of the NEE ( φ NEE ) during the photoperiod. The magnitude of the stimulation of NEE max , expressed per unit ground area, was seasonal, rising from 50% in the winter to 180% in the summer. The key to this stimulation was effects of elevated C a , and their interaction with the seasonal changes in the environment, on ecosystem leaf area index, photosynthesis and respiration. The separation of these factors was difficult. When expressed per unit leaf area the stimulation of the NEE max ranged from 7% to 60%, with the increase being dependent on increasing soil water content ( W soil ). At night, the CO 2 effluxes from the ecosystem ( NEE night ) were on an average 39% higher in elevated C a . However, the increase varied between 6% and 64%, and had no clear seasonality. The partitioning of NEE night into its belowground ( R below ) and aboveground ( R above ) components was carried out in the winter only. A 35% and 27% stimulation of NEE night in December 1999 and 2000, respectively, was largely due to a 26% and 28% stimulation of R below in the respective periods, because R below constituted ca. 87% of NEE night . The 37% and 42% stimulation of R above in December 1999 and 2000, respectively, was less than the 65% and 80% stimulation of the aboveground biomass by elevated C a at these times. An increase in the relative amount of the aboveground biomass in woody tissue, combined with a decrease in the specific rate of stem respiration of the dominant species Quercus myrtifolia in elevated C a , was responsible for this effect. Throughout this study, elevated C a had a greater effect on carbon uptake than on carbon loss, in terms of both the absolute flux and relative stimulation. Consequently, for this scrub–oak ecosystem carbon sequestration was greater in the elevated C a during this 2‐year study period.

Rhizosecretion of a monoclonal antibody protein complex from transgenic tobacco roots - Pascal M.W. Drake; Daniel M. Chargelegue; Nicholas D. Vine; Craig J. van Dolleweerd; Patricia Obregon; Julian K-C. Ma (Plant Molecular Biology, 2003)

Cross validation of open‐top chamber and eddy covariance measurements of ecosystem CO 2 exchange in a Florida scrub‐oak ecosystem - Sabina Dore; Graham J. Hymus; David P. Johnson; C. R. Hinkle; Riccardo Valentini; Bert G. Drake (Global Change Biology, 2003)
Simultaneous measurements of net ecosystem CO 2 exchange (NEE) were made in a Florida scrub‐oak ecosystem in August 1997 and then every month between April 2000 to July 2001, using open top chambers (NEE O ) and eddy covariance (NEE E ). This study provided a cross validation of these two different techniques for measuring NEE. Unique characteristics of the comparison were that the measurements were made simultaneously, in the same stand, with large replicated chambers enclosing a representative portion of the ecosystem (75 m 2 , compared to approximately 1–2 ha measured by the eddy covariance system). The value of the comparison was greatest at night, when the microclimate was minimally affected by the chambers. For six of the 12 measurement periods, night NEE O was not significantly different to night NEE E , and for the other periods the maximum difference was 1.1 µ mol m − 2 s − 1 , with an average of 0.72 ± 0.09 µ mol m − 2 s − 1 . The comparison was more difficult during the photoperiod, because of differences between the microclimate inside and outside the chambers. During the photoperiod, air temperature (T air ) and air vapour pressure deficits (VPD) became progressively higher inside the chambers until mid‐afternoon. In the morning NEE O was higher than NEE E by about 26%, consistent with increased temperature inside the chambers. Over the mid‐day period and the afternoon, NEE O was 8% higher that NEE E , regardless of the large differences in microclimate. This study demonstrates both the uses and difficulties associated with attempting to cross validate NEE measurements made in chambers and using eddy covariance. The exercise was most useful at night when the chamber had a minimal effect on microclimate, and when the measurement of NEE is most difficult.

Direct and indirect effects of elevated CO 2 on transpiration from Quercus myrtifolia in a scrub‐oak ecosystem - J.‐H. Li; W. A. Dugas; G. J. Hymus; D. P. Johnson; C. R. Hinkle; B. G. Drake; B. A. Hungate (Global Change Biology, 2003)
Elevated atmospheric carbon dioxide (C a ) usually reduces stomatal conductance, but the effects on plant transpiration in the field are not well understood. Using constant‐power sap flow gauges, we measured transpiration from Quercus myrtifolia Willd., the dominant species of the Florida scrub‐oak ecosystem, which had been exposed in situ to elevated C a (350 µmol mol − 1 above ambient) in open‐top chambers since May 1996. Elevated C a reduced average transpiration per unit leaf area by 37%, 48% and 49% in March, May and October 2000, respectively. Temporarily reversing the C a treatments showed that at least part of the reduction in transpiration was an immediate, reversible response to elevated C a . However, there was also an apparent indirect effect of C a on transpiration: when transpiration in all plants was measured under common C a , transpiration in elevated C a ‐grown plants was lower than that in plants grown in normal ambient C a . Results from measurements of stomatal conductance (g s ), leaf area index (LAI), canopy light interception and correlation between light and g s indicated that the direct, reversible C a effect on transpiration was due to changes in g s caused by C a , and the indirect effect was caused mainly by greater self‐shading resulting from enhanced LAI, not from stomatal acclimation. By reducing light penetration through the canopy, the enhanced self‐shading at elevated C a decreased stomatal conductance and transpiration of leaves at the middle and bottom of canopy. This self‐shading mechanism is likely to be important in ecosystems where LAI increases in response to elevated C a .

Seasonal variability in the effect of elevated CO 2 on ecosystem leaf area index in a scrub‐oak ecosystem - Graham J. Hymus; Jean‐Yves Pontailler; Jiahong Li; Peter Stiling; C. Ross Hinkle; Bert G. Drake (Global Change Biology, 2002)
We report effects of elevated atmospheric CO 2 concentration ( C a ) on leaf area index (LAI) of a Florida scrub‐oak ecosystem, which had regenerated after fire for between three and five years in open‐top chambers (OTCs) and was yet to reach canopy closure. LAI was measured using four nondestructive methods, calibrated and tested in experiments performed in calibration plots near the OTCs. The four methods were: PAR transmission through the canopy, normalized difference vegetation index (NDVI), hemispherical photography, and allometric relationships between plant stem diameter and plant leaf area. Calibration experiments showed: (1) Leaf area index could be accurately determined from either PAR transmission through the canopy or hemispherical photography. For LAI determined from PAR transmission through the canopy, ecosystem light extinction coefficient ( k ) varied with season and was best described as a function of PAR transmission through the canopy. (2) A negative exponential function described the relationship between NDVI and LAI; (3) Allometric relationships overestimated LAI. Throughout the two years of this study, LAI was always higher in elevated C a , rising from, 20% during winter, to 55% during summer. This seasonality was driven by a more rapid development of leaf area during the spring and a relatively greater loss of leaf area during the winter, in elevated C a . For this scrub‐oak ecosystem prior to canopy closure, increased leaf area was an indirect mechanism by which ecosystem C uptake and canopy N content were increased in elevated C a . In addition, increased LAI decreased potential reductions in canopy transpiration from decreases in stomatal conductance in elevated C a . These findings have important implications for biogeochemical cycles of C, N and H 2 O in woody ecosystems regenerating from disturbance in elevated C a .

Elevated atmospheric CO 2 lowers herbivore abundance, but increases leaf abscission rates - Peter Stiling; Maria Cattell; Daniel C. Moon; Anthony Rossi; Bruce A. Hungate; Graham Hymus; Bert Drake (Global Change Biology, 2002)
Increased levels of atmospheric carbon dioxide (CO 2 ) are likely to affect the trophic relationships that exist between plants, their herbivores and the herbivores' natural enemies. This study takes advantage of an open‐top CO 2 fertilization experiment in a Florida scrub oak community at Kennedy Space Center, Florida, consisting of eight chambers supplied with ambient CO 2 (360 ppm) and eight chambers supplied with elevated CO 2 (710 ppm). We examined the effects of elevated CO 2 on herbivore densities and levels of leaf consumption, rates of herbivore attack by natural enemies and effects on leaf abscission. Cumulative levels of herbivores and herbivore damage were significantly lower in elevated CO 2 than in ambient CO 2 . This may be because leaf nitrogen levels are lower in elevated CO 2 . More herbivores die of host plant‐induced death in elevated CO 2 than in ambient CO 2 . Attack rates of herbivores by parasitoids are also higher in elevated CO 2 , possibly because herbivores need to feed for a longer time in order to accrue sufficient nitrogen (N), thus exposing themselves longer to natural enemies. Insect herbivores cause an increase in abscission rates of leaves throughout the year. Because of the lower insect density in elevated CO 2 , we thought, abscission rates would be lower in these chambers. However, abscission rates were significantly higher in elevated CO 2 . Thus, the direct effects of elevated CO 2 on abscission are greater than the indirect effects on abscission mediated via lower insect densities. A consequence of increased leaf abscission in elevated CO 2 is that nutrient deposition rates to the soil surface are accelerated.

Elevated atmospheric CO 2 stimulates aboveground biomass in a fire‐regenerated scrub‐oak ecosystem - Paul Dijkstra; Graham Hymus; Debra Colavito; David A. Vieglais; Christina M. Cundari; David P. Johnson; Bruce A. Hungate; C. ROSS Hinkle; Bert G. Drake (Global Change Biology, 2002)
The effect of elevated atmospheric CO 2 concentration ( C a ) on the aboveground biomass of three oak species, Quercus myrtifolia , Q. geminata , and Q. chapmanii , was estimated nondestructively using allometric relationships between stem diameter and aboveground biomass after four years of experimental treatment in a naturally fire‐regenerated scrub‐oak ecosystem. After burning a stand of scrub‐oak vegetation, re‐growing plants were exposed to either current ambient (379 µL L −1 CO 2 ) or elevated (704 µL L −1 CO 2 ) C a in 16 open‐top chambers over a four‐year period, and measurements of stem diameter were carried out annually on all oak shoots within each chamber. Elevated C a significantly increased aboveground biomass, expressed either per unit ground area or per shoot; elevated C a had no effect on shoot density. The relative effect of elevated C a on aboveground biomass increased each year of the study from 44% (May 96–Jan 97), to 55% (Jan 97–Jan 98), 66% (Jan 98–Jan 99), and 75% (Jan 99–Jan 00). The effect of elevated C a was species specific: elevated C a significantly increased aboveground biomass of the dominant species, Q. myrtifolia , and tended to increase aboveground biomass of Q. chapmanii , but had no effect on aboveground biomass of the subdominant, Q. geminata . These results show that rising atmospheric CO 2 has the potential to stimulate aboveground biomass production in ecosystems dominated by woody species, and that species‐specific growth responses could, in the long term, alter the composition of the scrub‐oak community.

Global Redistribution of Bacterioplankton and Virioplankton Communities - Lisa A. Drake; Keun-Hyung Choi; Gregory M. Ruiz; Fred C. Dobbs (Biological Invasions, 2001)

Assembly and plasma membrane targeting of recombinant immunoglobulin chains in plants with a murine immunoglobulin transmembrane sequence - Nicholas D. Vine; Pascal Drake; Andrew Hiatt; Julian K.-C. Ma (Plant Molecular Biology, 2001)

An Evaluation of Restoration Efforts in Fishless Lakes Stocked with Exotic Trout - Deanne C. Drake; Robert J. Naiman (Conservation Biology, 2000)
Detrimental effects of introduced fishes on native amphibian populations have prompted removal of introduced cutthroat ( Oncorhynchus clarki ), rainbow ( Oncorhynchus mykiss ), and brook trout ( Salvelinus fontinalis ) from naturally fishless lakes at Mt. Rainier National Park, Washington ( U.S.A.). Using paleolimnological indicators (diatoms, invertebrates, and sediment characteristics) in eight 480‐year‐old sediment cores from eight lakes, we (1) derived estimates of baseline environmental conditions and natural variation, (2) assessed the effects of stocking naturally fishless lakes, and (3) determined whether lakes returned to predisturbance conditions after fish removal (restoration). Diatom floras were relatively stable between 315 and 90 years before present in all lakes; we used this time period to define lake‐specific “baseline” conditions. Dissimilarity analyses of diatoms revealed sustained, dramatic changes in diatom floras that occurred approximately 80 years ago (when fish were introduced) in four of five stocked lakes, whereas the diatom floras in two unstocked lakes had not changed significantly in the last 315 years. Diatoms were not preserved in an eighth lake. State changes also occurred in two lakes over 200 years before European settlement of the Pacific Northwest. Preserved invertebrate densities fluctuated dramatically over time in all cores, providing a poor reference for assessing the effects of fishes. Nevertheless, fish‐invertebrate interactions have been demonstrated in other paleolimnological studies and may be useful for lower‐elevation or more productive lakes. Because diatom communities have not returned to predisturbance assemblages in restored lakes, even 20–30 years after fish removal, we conclude that Mt. Rainier lakes were not successfully restored by the removal of fishes.

An Evaluation of Restoration Efforts in Fishless Lakes Stocked with Exotic Trout - Deanne C. Drake; Robert J. Naiman (Conservation Biology, 2000)

Leaf senescence of Quercus myrtifolia as affected by long‐term CO 2 enrichment in its native environment - J. ‐H. Li; P. Dijkstra; G. J. Hymus; R. M. Wheeler; W. C. Piastuch; C. R. Hinkle; B. G. Drake (Global Change Biology, 2000)
Summary The long‐term effects of elevated (ambient plus 350 μmol mol −1 ) atmospheric CO 2 concentration (C a ) on the leaf senescence of Quercus myrtifolia Willd was studied in a scrub‐oak community during the transition from autumn (December 1997) to spring (April 1998). Plants were grown in large open‐top chambers at the Smithsonian CO 2 Research Site, Merritt Island Wildlife Refuge, Cape Canaveral, Florida. Chlorophyll (a + b) concentration, Rubisco activity and N concentration decreased by 75%, 82%, and 52%, respectively, from December (1997) to April (1998) in the leaves grown at ambient C a . In contrast, the leaves of plants grown at elevated C a showed no significant decrease in chlorophyll (a + b) concentration or Rubisco activity, and only a 25% reduction in nitrogen. These results indicate that leaf senescence was delayed during this period at elevated C a . Delayed leaf senescence in elevated C a had important consequences for leaf photosynthesis. In elevated C a the net photosynthetic rate of leaves that flushed in Spring 1997 (last year's leaves) and were 13 months old was not different from fully‐expanded leaves that flushed in 1998, and were approximately 1 month old (current year's leaves). In ambient C a the net photosynthetic rate of last year's leaves was 54% lower than for current year's leaves. When leaves were fully senesced, nitrogen concentration decreased to about 40% of the concentration in non‐senesced leaves, in both CO 2 treatments. In April, net photosynthesis was 97% greater in leaves grown in elevated C a than in those grown at ambient. During the period when elevated C a delayed leaf senescence, more leaves operating at higher photosynthetic rate would allow the ecosystem dominated by Q. myrtifolia to gain more carbon at elevated C a than at ambient C a .

A murine monoclonal antibody produced in transgenic plants with plant-specific glycans is not immunogenic in mice - Daniel Chargelegue; Nicholas D. Vine; Craig J. van Dolleweerd; Pascal M.W. Drake; Julian K-C. Ma (Transgenic Research, 2000)

Elevated CO 2 increases nitrogen fixation and decreases soil nitrogen mineralization in Florida scrub oak - Bruce A. Hungate; PauL. Dijkstra; DalE. W. Johnson; C. RosS. Hinkle; BerT. G. Drake (Global Change Biology, 1999)
Summary We report changes in nitrogen cycling in Florida scrub oak in response to elevated atmospheric CO 2 during the first 14 months of experimental treatment. Elevated CO 2 stimulated above‐ground growth, nitrogen mass, and root nodule production of the nitrogen‐fixing vine, Galactia elliottii Nuttall. During this period, elevated CO 2 reduced rates of gross nitrogen mineralization in soil, and resulted in lower recovery of nitrate on resin lysimeters. Elevated CO 2 did not alter nitrogen in the soil microbial biomass, but increased the specific rate of ammonium immobilization (NH 4 + immobilized per unit microbial N) measured over a 24‐h period. Increased carbon input to soil through greater root growth combined with a decrease in the quality of that carbon in elevated CO 2 best explains these changes. These results demonstrate that atmospheric CO 2 concentration influences both the internal cycling of nitrogen (mineralization, immobilization, and nitrification) as well as the processes that regulate total ecosystem nitrogen mass (nitrogen fixation and nitrate leaching) in Florida coastal scrub oak. If these changes in nitrogen cycling are sustained, they could cause long‐term feedbacks to the growth responses of plants to elevated CO 2 . Greater nitrogen fixation and reduced leaching could stimulate nitrogen‐limited plant growth by increasing the mass of labile nitrogen in the ecosystem. By contrast, reduced nitrogen mineralization and increased immobilization will restrict the supply rate of plant‐available nitrogen, potentially reducing plant growth. Thus, the net feedback to plant growth will depend on the balance of these effects through time.

Comparison of a beet curly top virus isolate originating from the old world with those from the new world - Rob W. Briddon; Drake C. Stenger; Ian D. Bedford; John Stanley; Keramatollah Izadpanah; Peter G. Markham (European Journal of Plant Pathology, 1998)

Effects of copper-contaminated sediments on Hyalella azteca, Daphnia magna, and Ceriodaphnia dubia: Survival, growth, and enzyme inhibition - J. A. Kubitz; E. C. Lewek; J. M. Besser; J. B. Drake; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 1995)